The Role of ATP-Binding Cassette Transporters in Neuro-Inflammation: Relevance for Bioactive Lipids - Kooij, Gijs; van Horssen, Jack; Bandaru, Veera Venkata Ratnam; Haughey, Norman J.; De Vries, Helga E. (Frontiers in Pharmacology, 2012)
ATP-binding cassette (ABC) transporters are highly expressed by brain endothelial cells that form the blood–brain barrier (BBB). These efflux pumps play an important role in maintaining brain homeostasis as they actively hinder the entry of unwanted blood-derived compounds into the central nervous system (CNS). Consequently, their high activity at the BBB has been a major hurdle for the treatment of several brain diseases, as they prevent numerous drugs to reach their site of action within the brain. Importantly, recent data indicate that endogenous substrates for ABC transporters may include inflammatory mediators, such as prostaglandins, leukotrienes, cytokines, chemokines, and bioactive lipids, suggesting a potential role for ABC transporters in immunological responses, and more specifically in inflammatory brain disorders, such as multiple sclerosis (MS). In this review, we will give a comprehensive overview of recent findings that illustrate this novel role for ABC transporters in neuro-inflammatory processes. Moreover, we will provide first insights into underlying mechanisms and focus on the importance for bioactive lipids, in particular platelet-activating factor, herein. A thorough understanding of these events may form the basis for the development for selective treatment modalities to dampen the neuro-inflammatory attack in MS and thereby reducing tissue damage.